Superconductive REBCO Thin Films and Their Nanocomposites: The Role of Rare-Earth Oxides in Promoting Sustainable Energy - Jha, Alok K.; Matsumoto, Kaname (Frontiers in Physics, 2019)
The lossless transmission of direct electrical currents in superconductors is very often regarded as an “energy superhighway” with greatly enhanced efficiency. With the discovery of high temperature superconductors (HTS) in the late eighties, the prospect of using these materials in efficient and advanced technological applications became very prominent. The elevated operating temperatures as compared to low temperature superconductors (LTS), relaxing cooling requirements, and the gradual development of facile synthesis processes raised hopes for a broad breakthrough of superconductor technology. The impact of superconductor technology on the economy and energy sectors is predicted to be huge if these are utilized on a large scale. The development of superconducting tapes with high critical current density (Jc) is crucial for their use in transmission cables. Many countries these days are running projects to develop wires from these HTS materials and simultaneously field trials are being conducted to assess the feasibility of this technology. These HTS wires can carry electrical currents more than 100 times larger than their conventional counterparts with minimal loss of energy. The increased efficiency of HTS electric power products may result in greatly reduced carbon emissions compared to those resulting from using the conventional alternatives. In order to use the thin films of YBa2Cu3O7−δ (YBCO) and REBCO [RE (rare-earth) = Sm, Gd, Eu etc.], members of the HTS family, for future technological applications, the enhancement of Jc over wide range of temperatures and applied magnetic fields is highly desired. The enhancement of Jc of YBCO and REBCO films has been successfully demonstrated by employing different techniques which include doping by rare-earth atoms, incorporating nanoscale secondary phase inclusions into the REBCO film matrix, decoration of the substrate surface etc. which generate artificial pinning centers (APCs). In this review, the development of the materials engineering aspect that has been conducted over the last two decades to improve the current carrying capability of HTS thin films is presented. The effect of controlled incorporation of APCs through various methods and techniques on the superconducting properties of YBCO and REBCO thin films is presented, heading toward superior performance of such superconducting thin films.